Factors Associated With Late Surgical Cancellations in Pediatric Plastic and Oral Surgery. Issue 4 (April 2018) - Beijnen, Usha E.A.; Noonan Caillouette, Catherine; Flath-Sporn, Susan J.; Maclellan, Reid A.; Sanchez, Karl; Labow, Brian I.; Meara, John G.; Taghinia, Amir H.
Abstract : Background: Surgical cancellations that occur within 1 day of the procedure (ie, late cancellations) disrupt the efficiency of the operating room. The aim of the present study was to identify the factors associated with late cancellations in a tertiary pediatric surgical practice. Methods: We reviewed the medical records of patients treated by plastic and oral surgery services at our institution from 2010 to 2015. We collected data pertaining to the timing and reasons for cancellation. Reasons for cancellation were retrospectively classified by the investigators as either "preventable, " "possibly preventable, " "unpreventable, " or "undocumented." We also measured the frequency of cancellations based on type of surgery. Results: Of 10, 730 scheduled operating room cases, 444 (4.1%) were cancelled within 24 hours of the procedure. Sixty-seven percent (297/444 cases) were cancelled on the same day as the planned procedure, and the remaining cases were cancelled the day prior after 1 PM. Forty-two percent of cancellations were deemed preventable, and 45.3% of cases were deemed possibly preventable. The majority of procedures were cancelled because of illness (44%), inadequate fasting (9%), and parental inconvenience (7%). The highest frequency of cancellation was found in skin lesion (36%) followed by dentoalveolar (14%) and cleft lip and palate (12%) cases. Conclusions: In our study, most late surgical cancellations were preventable or possibly preventable. The timing of the cancellation is important because those that occur near the scheduled procedure time disallow adequate and timely redistribution of operating room resources and personnel. Analyzing and addressing the preventable and possibly preventable causes outlined in this study will significantly improve efficiency and patient access.